Sacral agenesis associated with teratoma: report of a case - Antonio Cesar G. Borges; Rodinei Roberto Festugato; José Carlos S. de Cerqueira; Miguel Ramos de Souza (Arquivos de Neuro-Psiquiatria)
A case of a 29-year-old male with a huge sacrococcygeal teratoma completely removed by surgery, and associated with a sacral agenesis is reported. Roentengenograms revealed fusion of the T12, LI, L2 and L3 vertebral bodies, absence of the left 12th rib, partial agenesis of sacrococcygeal elements and a lumbar scoliosis convex to the left. Cystometry and myelograms were normal. No such association has been found in the literature reviewed. Some topics on the embryology of these lesions are discussed.